ISOLATION AND SCREENING OF LEAD-TOLERANT BACTERIA FROM CEMENT CONTAMINATED SOIL FOR POTENTIAL BIOREMEDIATION APPLICATIONS - Vyas, Charu; Waoo, Ashwini A. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Bioremediation of metallic pollutants using heavy metal-tolerant bacteria is crucial to environmental biotechnology. This biological process involves the removal of heavy metals from contaminated areas. The first step in bioremediation is the screening of metal-tolerant bacteria. In this study, the soil contamination level of a cement plant was investigated by measuring the concentration of certain heavy metals. This study aimed to screen lead-tolerant bacterial strains from contaminated cement soil for use in bioremediation. Sixteen lead-tolerant strains were isolated from the soil of the two cement plant areas. The strains exhibited varying levels of tolerance to lead, with minimal inhibitory concentrations (MIC) ranging from 15 to 33 mg L-1. The most tolerant strains were selected for further research to assess their potential for bioremediation. The metal tolerance levels of a bacterial community isolated from a cement dust-polluted soil environment were assessed using different methods, including agar dilution, gradient plate, and MIC. The results showed that the bacteria were able to tolerate high concentrations of lead and that the MIC method was the most effective in evaluating their tolerance. For further studies, most tolerant isolates were selected with maximum MIC values, including BCN-B1/5/Pb and BCN-B1/9/Pb from the BCN-B1 sample and PCN-P1/1/Pb from the PCN-P1 sample. These isolates demonstrated high tolerance to lead, with MIC values of 33, 33, and 31 mg L-1, respectively.